CLIMATE VARIABILITY IMPACTS ON FOOD CROP PRODUCTION IN KIENI WEST SUB-COUNTY, KENYA - Kariuki, Godhard Muiruri; Joseph Kariuki Muriithi; Baaru, Mary Wamuyu (International Journal of Research -GRANTHAALAYAH, 2025)
Climate change and variability has hampered global agricultural growth and is anticipated to have a notable impact on crop production owing to the high reliance of agricultural activities on weather. The study examined impact of climate variability on production of major food crops (maize, beans and Irish potatoes) in Kieni West sub-County, Kenya. Mixed methods research design was used. Pearson’s coefficient of correlation (r) was used to assess the relationship between climate variables and the major food crops. Multiple Linear Regression (MLR) was employed to assess the effect of rainfall and temperature variability on major food crops. Analysis of quantitative data was done using descriptive and inferential statistics while analysis of qualitative data was done thematically. Data presentation was by use of figures, tables and verbatim quotes. Correlation results revealed a positive relationship between rainfall and bean (r = 0.46) and maize production (r = 0.33) and a negative relationship between rainfall and Irish potatoes production (r = -0.056). A negative relationship between maximum temperatures and production of bean (r = -0.89) and maize (r = -0.56) was observed while a positive relationship between maximum temperatures and production of Irish potatoes (r = 0.02) was reported. Also, correlation results revealed a negative relationship between minimum temperatures and production of maize (r = -0.35), beans (r = -0.43) and Irish potatoes (r = -0.38). Coefficient of Determination (R2) value of 0.11, 0.18, 0.003 for maize, beans and Irish potatoes respectively against rainfall was reported. R2 values of 0.32, 0.80 and 0.00 was reported for maize, beans and Irish potatoes respectively against maximum temperatures while R2 values of 0.12, 0.18 and 0.14 was reported for maize, beans and Irish potatoes respectively against minimum temperatures. The study concludes that climate variability had differential impacts on production of maize, beans and Irish potatoes in the study area.